The Network Theory of Well-Being: An Introduction - Michael Bishop (Baltic International Yearbook of Cognition, Logic and Communication, 2012)
In this paper, I propose a novel approach to investigating the nature of well-being and a new theory about well-being. The approach is integrative and naturalistic. It holds that a theory of well-being should account for two different classes of evidence – our commonsense judgments about well-being and the science of well-being (i.e., positive psychology). The network theory holds that a person is in the state of well-being if she instantiates a homeostatically clustered network of feelings, emotions, attitudes, behaviors, traits, and interactions with the world that tends to have a relatively high number of states that feel good, that lead to states that feel good, or that are valued by the agent or her culture.